Comparison of Chronic Heavy Metal Contamination Level in the Body Between Chemical Pesticide Sprayers and General Public Around Agricultural Areas - Renaningtyas Nityasani; Khuliyah Candraning Diyanah; Wicaksono, Rania Ichwana; Muhammad Azmi Maruf; Zainul Amiruddin Zakaria; Aditya Sukma Pawitra (JURNAL KESEHATAN LINGKUNGAN, 2025)
Introduction: The increasing use of chemical pesticides in agriculture raises concerns about heavy metal exposure. This study compares chronic heavy metal contamination levels (Pb, Cd, Cr6+) in the urine of pesticide sprayers and the general public in agricultural areas. Methods: A cross-sectional study with 100 respondents, equally divided between sprayers and the general public, was conducted. Data were gathered through interviews, observations, and laboratory tests. Heavy metal levels in urine were analyzed using Atomic Absorption Spectroscopy (AAS). Factors like age, work duration, spraying frequency, and Personal Protective Equipment (PPE) use were examined through Mann-Whitney and linear regression tests. Results and Discussion: Pesticide sprayers had significantly higher mean levels of Pb (0.084 mg/kg), Cd (0.010 mg/kg), and Cr6+ (0.010 mg/kg) than the general public. Key contributors to this accumulation included age, working hours, and the number of pesticide mixtures used. Inadequate PPE use and long exposure times were common, leading to health complaints such as nausea, vomiting, and headaches, indicating the harmful effects of pesticide exposure. Conclusion: Pesticide sprayers are at greater risk of heavy metal accumulation due to prolonged exposure and poor safety measures. Improving PPE use and reducing exposure are critical to minimizing health risks from heavy metal contamination. Awareness campaigns are necessary to protect agricultural workers.